Overhead perturbation training - Burne, G.; Tack, C. (Strength and Conditioning Journal, 2017)
Overhead physical performance of the upper limb is predicated on various factors including proprioception, kinesthesia, and muscle activity around the glenohumeral and scapulothoracic joints. Sustaining sufficient neuromuscular control allows optimal performance to occur, while reducing risk of injury. Conversely, both factors are reduced in the presence of an injury showing their importance in rehabilitation. Overhead perturbation training allows controlled exposure of the athlete to positions of vulnerability to allow facilitation of adaptive responses to improve response to external perturbations of limb position. This technique allows development of neuromuscular control patterns that may reduce injury.